2017
DOI: 10.1186/s12955-017-0676-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychological status and quality of life among primary caregivers of individuals with mental illness: a hospital based study

Abstract: BackgroundThis study aimed to explore the psychological status and quality of life among primary caregivers of individuals suffering from various mental illnesses including early psychosis, chronic schizophrenia, depressive disorders, anxiety disorders and dementia.MethodsA total of 350 primary caregivers with relatives seeking treatment at a tertiary psychiatric hospital were recruited for this study. Socio-demographic data was obtained and the brief version of the World Health Organisation Quality of Life in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 37 publications
7
56
0
5
Order By: Relevance
“…As a result, families, especially in Chinese society, play a significant role in care provision for relatives with schizophrenia . However, the burden of caregiving has been shown to cause a range of psychological and emotional distress among caregivers in many parts of the world . This study aimed to assess the degree of stress and burden among caregivers of relatives with schizophrenia and early psychosis in Hong Kong and to identify suitable measures to support them.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, families, especially in Chinese society, play a significant role in care provision for relatives with schizophrenia . However, the burden of caregiving has been shown to cause a range of psychological and emotional distress among caregivers in many parts of the world . This study aimed to assess the degree of stress and burden among caregivers of relatives with schizophrenia and early psychosis in Hong Kong and to identify suitable measures to support them.…”
Section: Introductionmentioning
confidence: 99%
“…Just as critically, there is significant scope to improve employment participation for those carers who do want to return to work. There are a range of benefits for carers to their finances, health and satisfaction from working (Chou, Pu, Kröger, & Fu, ; Jeyagurunathan et al, ). Mental health carers’ reported barriers to re‐entering the workforce were more centred on the needs of the people they support than the suitability of the workforce or carers’ own skills.…”
Section: Discussionmentioning
confidence: 99%
“…However, another similar study conducted in Singapore found much lower scores in the psychological domain in spousal caregivers as opposed to parental caregivers (22).…”
mentioning
confidence: 88%